2015
DOI: 10.1155/2015/501508
|View full text |Cite
|
Sign up to set email alerts
|

Oldenlandia diffusaPromotes Antiproliferative and Apoptotic Effects in a Rat Hepatocellular Carcinoma with Liver Cirrhosis

Abstract: Oldenlandia diffusa (OD) is commonly used with various diseases such as cancer, arthritis, and autoimmune disease. Liver cirrhosis is a predominant risk factor for hepatocellular carcinoma (HCC). Here, we show that the therapeutic effect of OD, which was investigated both in vitro and chemically, induced HCC model. OD significantly enhanced apoptosis and antiproliferative activity and reduced migration ability of HCC cells. In vivo, OD was treated twice a day for 28 days after confirmed HCC model through 2-[18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 34 publications
(32 reference statements)
1
16
0
Order By: Relevance
“…Recently, anti-amnestic activity has been reported from natural products such as pine needle extract [ 19 ], Avena sativa extract [ 20 ] and Actinidia argute extract [ 21 ]. The extract of Oldenlandia diffusa is reported to have anti-inflammatory [ 22 ] and anti-cancer activity in colorectal [ 23 ], liver [ 24 ] and breast cancers [ 25 ]. Furthermore, its compounds such as ursolic acid and oleanolic acid were reported for their anti-amnestic and neuroprotective effects [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, anti-amnestic activity has been reported from natural products such as pine needle extract [ 19 ], Avena sativa extract [ 20 ] and Actinidia argute extract [ 21 ]. The extract of Oldenlandia diffusa is reported to have anti-inflammatory [ 22 ] and anti-cancer activity in colorectal [ 23 ], liver [ 24 ] and breast cancers [ 25 ]. Furthermore, its compounds such as ursolic acid and oleanolic acid were reported for their anti-amnestic and neuroprotective effects [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, some previous studies demonstrated that H. diffusa Willd can induce apoptosis in ovarian cancer cells, leading to the inhibition of tumor growth in hepatocellular carcinoma (15,16). To verify this, we tested the viability of TC-1 cells treated with BHSSC.…”
Section: Discussionmentioning
confidence: 95%
“…Among frequently used forms of CHM, Hedyotis diffusa Willd (Bai Hua She She Cao, BHSSC) is associated with a reduced hazard ratio for mortality risk in nasopharyngeal carcinoma and breast cancer (9,12,14). Moreover, previous investigations have shown that H. diffusa Willd possesses important pharmacological activities and is capable of inducing apoptosis in ovarian cancer cells and inhibiting cell proliferation in hepatocellular carcinoma (15,16). However, the role of H. diffusa Willd in the regulation of the immune response and its therapeutic effect on HPV-related cancer have not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Based on HPLC analysis, MOD has 15 times and 5 times greater amounts of UA and OA, respectively, compared to WOD. OD extract has been reported to include asperuloside, E-6-O-p-coumaroyl scandoside methyl ester, and E-6-O-p-coumaroyl scandoside methyl ester-10-methyl ether, in addition to UA and OA [6]. Individual and combined treatment with UA and OA showed relatively mild cytotoxic effects compared to MOD itself, suggesting that other compounds in MOD might contribute to MOD effects on cell viability.…”
Section: Discussionmentioning
confidence: 99%
“…Ursolic acid and oleanolic acid have been reported to have anti-tumor, apoptotic, antioxidant, cytotoxic, and anti-angiogenic activity, and anti-inflammatory effects [4,5]. Extracts of OD have also been reported to have anticancer effects [6,7]. Treatment of human breast cancer MCF-7 cells with OD extracts induced cell death through increased expression and activation of apoptosis-related proteins [8].…”
Section: Introductionmentioning
confidence: 99%